Evaluation of Achievement Development Programs Using the Cipp Model for Sepak Takraw in Demak Regency - Fadila Ainun Nisa; Agus Raharjo (Universitas Negeri Semarang, 2025)
The achievement coaching program is a program used by local governments to improve the performance of athletes in various sports. One of the programs implemented by the Demak Regency Government is to enhance the achievements in sepak takraw. This research describes the achievement coaching program for sepak takraw in Demak Regency and evaluates the program using the CIPP model (Context, Input, Process, Product) as well as the obstacles that occurred during the coaching and evaluation process. The method used is qualitative, with primary and secondary data analyzed using descriptive presentation. Data and information were collected through secondary document observation, observation, and interviews with relevant stakeholders. The results show that performance improvement uses 3 main programs, namely the achievement coaching program, education and training for athletes, and coach development. Meanwhile, the evaluation findings in the Context indicate that there is consistency between the vision and mission and that the formulation of the vision and mission is objective. Input on find 4 aspects of analysis namely Human Resources, training programs, funding, and infrastructure. The PSTI process has adopted management principles including planning, organizing, leading, and controlling, in addition to coordination and implementation. Finally, there is a product analysis that measures the success of the achievement coaching program from several sub-aspects, namely the results of the program, academic achievements, national achievements, Asian achievements, and Asian Games achievements. There are hurdles, namely public enthusiasm to become athletes, budget constraints, and motivation.